2014
DOI: 10.2478/rrlm-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the phosphorylated neurofilament subunit NF-H (pNF-H) in cerebro-spinal fluid as biomarker in acute traumatic spinal cord injuries / Dozarea neurofilamentelor fosforilate (subunitatea pNF-H) ȋn LCR ca biomarker ȋn traumatismul vertebro-medular acut

Abstract: Study objective. The objective of this study was to measure the phosphorylated neurofilament subunit NF-H (pNF-H)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Ungureanu et al . () confirmed a substantial increase in CSF levels of heavy subunit of neurofilaments during the first 3 days between SCI patients and the control group. However, Hoska et al .…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Ungureanu et al . () confirmed a substantial increase in CSF levels of heavy subunit of neurofilaments during the first 3 days between SCI patients and the control group. However, Hoska et al .…”
Section: Resultssupporting
confidence: 57%
“…In another study with a 12–18‐months follow up of patients, Ungureanu et al . () showed that this biomarker is able to predict the outcome of patients when measured in the first 6 h, but its levels do not show a significant difference when measured after 24 h.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies suggested the utility of cerebrospinal fluid (CSF) neurofilaments for cerebrovascular and spinal pathology (2,3), but this type of sampling is more invasive and prone to severe side effects. As an important structural protein in neurons, increased concentration of neuro-filaments in peripheral blood might mirror the neuronal destruction in various central nervous system (CNS) disorders and to be considered a potential marker for axonal damage, detectable now in peripheral blood by sensitive ELISA methods (4), being at the same time a causative agent for neurological diseases and a marker for disease progression (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ungureanu et al . [ 17 ] did serial estimation of pNF-H in CSF of 15 patients with SCI (both cervical and dorsal) and concluded that it is an important predictor of severity of SCI and is sensitive to secondary lesions.…”
Section: Discussionmentioning
confidence: 99%